Pengaruh Pelatihan dan Motivasi Kerja Terhadap Kinerja Kerja Karyawan PT Asia Multidana di Jakarta - Okky Pratama (Universitas Tarumanagara, 2020)
This study was to detect the effect of training and motivation on employee performance studies in the limited partnership. This research was conducted with survey method and performed in 40 employees of PT Asia Multidana. The sampling technique used random sampling and testing techniques of data used in this study include tests of validity by factor analysis, reliability tests with Cronbach alpha, classical assumption test, multiple linear regression analysis, t test to test and prove the hypothesis of the study. The data collected is tested for validity by factor analysis method and tested reliability with an alpha coefficient (Cronbach alpha), which is the result of all the data is valid and reliable. The results of the analysis and discussion show that: (1) training positively affect the performance of employees, (2) positive motivation does not affect the performance of the employee.